2012
DOI: 10.3378/027.084.0205
|View full text |Cite
|
Sign up to set email alerts
|

The Family Name as Socio-Cultural Feature and Genetic Metaphor: From Concepts to Methods

Abstract: A recent workshop entitled ''The Family Name as Socio-Cultural Feature and Genetic Metaphor: From Concepts to Methods" was held in Paris in December 2010, sponsored by the French National Centre for Scientific Research (CNRS) and by the journal Human Biology. This workshop was intended to foster a debate on questions related to the family names and to compare different multidisciplinary approaches involving geneticists, historians, geographers, sociologists and social anthropologists. This collective paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Crow and Mange (1965) developed the idea that the degree of inbreeding in a population could be calculated from the frequency of isonymous marriage, leading to a stream of population studies (see, e.g., Lasker, 1968;Gottlieb, 1983;Barrai et al, 1999). Studies in anthropology and genetics have found that the distribution of surnames in patrilineal societies is similar to that of the neutral alleles of a gene transmitted only through the Y-chromosome (Yasuda and Morton, 1967;Yasuda and Furusho, 1971;Yasuda et al, 1974;Zei et al, 1983a,b), and indeed to that of any social or cultural trait, which is vertically transmitted from father to children and does not provide an intrinsic reproductive advantage (Cavalli-Sforza and Feldman, 1981;Cavalli-Sforza et al, 2004;Darlu et al, 2012). Crow (1983) states: "Surnames provide a quick, easy, cheap, and crude way to study human inbreeding and migration.…”
Section: Social Closure and Surname Diversitymentioning
confidence: 99%
“…Crow and Mange (1965) developed the idea that the degree of inbreeding in a population could be calculated from the frequency of isonymous marriage, leading to a stream of population studies (see, e.g., Lasker, 1968;Gottlieb, 1983;Barrai et al, 1999). Studies in anthropology and genetics have found that the distribution of surnames in patrilineal societies is similar to that of the neutral alleles of a gene transmitted only through the Y-chromosome (Yasuda and Morton, 1967;Yasuda and Furusho, 1971;Yasuda et al, 1974;Zei et al, 1983a,b), and indeed to that of any social or cultural trait, which is vertically transmitted from father to children and does not provide an intrinsic reproductive advantage (Cavalli-Sforza and Feldman, 1981;Cavalli-Sforza et al, 2004;Darlu et al, 2012). Crow (1983) states: "Surnames provide a quick, easy, cheap, and crude way to study human inbreeding and migration.…”
Section: Social Closure and Surname Diversitymentioning
confidence: 99%
“…The emigration patterns to other provinces that are mentioned in the Results section (Isolation-by-Distance, Gravity Deformed, and Long Distancesee Figure 5) represent a sandwich of phenomena that took place over four centuries with an unknown tempo, and unfortunately do not provide evidence for back-migration phenomena. We suggest that the Isolation by Distance patterns are the result of population diffusion that took place over a long time and largely correspond to the short migrations associated to marriages (Darlu et al 2012). Differently, the Gravity-Deformed and Long-Distance patterns are probably related to the 20th century's social changes of the country (urbanization, industrialization, abandonment of mountainous and rural areas) and to the advent of mechanized transportation.…”
Section: Mobility Of Italian Populations Since the Late Middle Ages: mentioning
confidence: 81%
“…Nevertheless, linguistic differences are insufficient to explain the observed regionalism of polyphyletic surnames, as many of them would be spelled almost in the same way all over the Italian peninsula, what very often does not happen. The fact that their distribution appears to be regional points to more complex socio-demographic and historical dynamics that go beyond the purposes of this paper (for a more general overview of them, see Darlu et al 2012). …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations